2016
DOI: 10.1007/s10661-016-5636-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the environmental carrying capacity of a freshwater tropical lake system

Abstract: Environmental carrying capacity is a measure of competence of a lake to accommodate pollution inputs without degrading water quality. In the research reported here, we identified the factors influencing the environmental carrying capacity of Vellayani Lake or VL (a typical tropical freshwater lake), Thiruvananthapuram, Kerala State, India. R-mode factor analysis is used to identify the factors controlling the carrying capacity of the lake, whereas hierarchical cluster analysis (HCA) helped to classify the lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…④ The correlation coefficient and the correlation degree between the indicator sequence and the reference series are calculated based on the absolute difference sequence [20]:…”
Section: Gray Correlation Modelmentioning
confidence: 99%
“…④ The correlation coefficient and the correlation degree between the indicator sequence and the reference series are calculated based on the absolute difference sequence [20]:…”
Section: Gray Correlation Modelmentioning
confidence: 99%
“…After continuously enriching the definition of RECC, scholars have begun to study methods and models. At present, the main evaluation methods for resource and environmental sustainability are environmental impact assessment [ 30 ], ecological footprint method [ 31 ], emergy analysis [ 32 , 33 ], and cluster analysis [ 34 , 35 ]. The main methods for determining the weight of the RECC index system are entropy method and analytic hierarchy process [ 36 38 ].…”
Section: Interactive Framework Of Reccmentioning
confidence: 99%
“…Groundwater resources are also affected by human activities and climate change. It is reported that a decrease in groundwater resources has occurred in major groundwater exploitation areas around the world [10][11][12][13]. The annual decrease rate of groundwater resources in the high plains of the United States, northwest India and the North China Plain are all serious [14].…”
Section: Introductionmentioning
confidence: 99%